The Italian Mezzogiorno: From a "National Matter" to an "European Opportunity" - Claudio Genna Vincenzo (European Regional Science Association (ERSA), 2006)
The aim of the paper is to analyze the present economic conditions of Southern Italy, particularly regarding the actual competitiveness of this region and possible future developments. We will outline the various features of Southern Italy economy giving emphasis to those limiting its competitiveness and, subsequently, suggesting opportune ways to improve it. Besides an opportunity coming from the international economic scenario, Southern Italy also has a great chance for its development from its traditional sectors. Moreover, it has really important environmental and cultural capitals which, besides an important touristical attractive, represent a potential of competitiveness able to start up development processes. The geographical position of Southern Italy can also bring significant advantages: Mezzogiorno is right in the middle of the mediterranean area which is showing high development potentials and is itself a large potential market. Regarding the institutional and political context, the governmental capacity of local administrations has improved over the last years and they started to pay more attention to increasing and promoting territories' resources. There has also been a major ability to face criminality and corruption and a new "social disapproval" towards illegal phenomena is growing. Among weaknesses the infrastructural endowment still seems to be inadequate. Transportation infrastructures present low integration between the different modalities with the consequence of difficult reachable market outflows. Logistic systems are still underdeveloped. Negative features are also present within the productive system. Traditional businesses with scarce innovation capacity are still too strong and generally the whole system is not improving network connections and scales economy. Then bureaucracy, even though much less than in the past, is an obstacle especially regarding the start-up of new firms. A big threat is represented by the growing competitiveness of developing countries in some traditional sectors of Mezzogiorno production. Final recommendations will result from the analysis of the actual and perspective economic situation compared with the main developments of global economy.
Keywords: 330